Association between prudent diet, sweet food consumption, and the risk of stress, anxiety, and depression among Indonesian students - Rohmah Mayasari Noor; Maya Shofia Naila; Anisfatus Sholihah Lini; Ruhana Amalia; Yanuar Dini Cleonara (BIO Web of Conferences)
Mental health disorders are prevalent among students. A cross- sectional survey was conducted to investigate the relationship between prudent-diet and sweet food with the risk of stress, anxiety, and depression among Indonesian students. The study involved 190 Indonesian students, aged above 19 years, who completed online questionnaires, including DASS, HFIAS, and FFQ. Students were recruited through various social media platforms. Principal component analysis was used to determine prudent-diet and sweet food among the respondents. Logistic regression was used to predict the association between prudent diet and sweet food on stress, anxiety, and depression among students. Prudent-diet is identified by fruits and vegetables, animal/plant-based protein, whole grains, sweet food, and low consumption of processed meats/fish. Incorporating sweets into a prudent-diet was associated with 22% reduced stress and 8% reduced anxiety among Indonesian students.